Biofortification Priority Index (BPI), a composite crop-specific index that ranks countries according to their suitability for investment in biofortification - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
In 2021, HarvestPlus updated the BPI with new varieties released data and the latest evidence on impact.